Discrepancies between Cyclic and Linear Antimicrobial Peptide Actions on the Spectrochemical and Nanomechanical Fingerprints of a Young Biofilm - Freudenthal, Oona (ACS Omega, 2017)
[Image: see text] Antimicrobial peptides (AMPs) are currently known for their potential as an alternative to conventional antibiotics and new weapons against drug-resistant bacteria and biofilms. In the present work, the mechanism of action of a cyclic (colistin) and a linear (catestatin) AMP on a young E. coli biofilm was deciphered from the molecular to the cellular scale. To this end, infrared spectroscopy (attenuated total reflection–Fourier transform infrared) assisted by chemometric analysis was combined with fluorescence and atomic force microscopies to address the very different behaviors of both AMPs. Indeed, the colistin dramatically damaged the bacterial cell wall and the metabolism even though its action was not homogeneous over the whole bacterial population and repopulation can be observed after peptide removal. Conversely, catestatin did not lead to major damages in the bacterial morphology but its action was homogeneous over the whole bacterial population and the cells were unable to regrow after the peptide treatment. Our results strongly suggested that contrary to the cyclic molecule, the linear one is able to cause irreversible damages in the bacterial membrane concomitantly to a strong impact on the bacterial metabolism.